Gameta masculino de mico-leão-de-cara-dourada (Leontopithecus chrysomelas): parâmetros reprodutivos seminais e epigenéticos - Watanabe, Isabela Midori (2015)
The Golden-headed lion tamarin (Leontopithecus chrysomelas) is an endemic monkey to Atlantic Forest. Nowadays, they are classified as threatened of extinction. Efforts on its conservation cover in situ and ex situ programs, and the application of the biotechnology of reproduction could assist populational manegement, hence ensuring the maintence of genetically healthy populations. Therefore, it is necessary to understand species reproductive characteristics, such as seminal parameters and variables that could influence them, and also the epigenetic mechanisms involved on genomic imprinting - once they are associated with reproductive success, and alterations on its patterns have been correlated with assisted reproduction technics. In the present study we investigated seminal and molecular parameters of golden-headed lion tamarins’ male gametes that are kept in captivity at São Paulo Zoological Foundation. Two main groups were outlined: seniors (mean age of 148.17 months; n=6) and young (mean age=50.14 months; n=6). Considering all animals, we could not find influence of weight on seminal parameters, as oppose to inbreeding coefficient variable, that showed negative correlation with total motility (R= -0.380, p<0.001), progressive motility (R= -0.443, p<0.001) and plasmatic membrane integrity (R= -0.270, p=0.018). Among seminal parameters, we found positive correlations between progressive motility and total motility (R=0.859, p=0.001), progressive motility and acrosome integrity (R=0.631, p=0.041), acrosome integrity and plasmatic membrane integrity (R=0.629, p=0.042). In addition, we found negative correlation between seminal pH and concentration (R= -0.612, p=0.029). There was only significant difference between seminal pH considering seniors and young males (t(9)=2.45, p=0.04), in which the seniors showed more alkaline pH. Molecular parameters investigated on these primates semen involved methylation analysis of two maternal imprinted genes: PEG3 and PEG1/MEST. Based on Callithrix jacchus genome, we inferred genes and its CpG islands to study them in L. chrysomelas. Through bisulfite sequencing, we investigated these regions of PEG3 and PEG1/MEST aiming to analyze putative DMRs. Among sampled animals, we could not find methylation differences on these regions, wherein all samples showed hypermethylated PEG3 region, and hipomethylated PEG1/MEST region. PEG3 CpG island is located in an exon, suggesting it is not involved in an imprinting control region. However, PEG1/MEST CpG island locates at a promoter region, showing hipomethylaton -as expected-, and align with PEG1/MEST promoter in humans, which could indicate a potential DMR. Our results are insipient to draw a conclusion about these imprinted genes in L. chrysomelas, but it was relevant as an initial approach to contribute to populational manegement of golden-headed lion tamarins kept in captivity.